Autism School di Batang dengan Prinsip Universal Design - Listyani, Marinta; , Dr. Ir. Widyastuti Nurjayanti, MT; , Yayi Arsandrie, ST., MT (2016)
Batang city is one of the small-town that existed in the province of Central Java. The city does not yet have school of autism, only have one SLB that inadequate facilities for children in need special. If seen from the number of autistic children in Batang City the longer growing, so the required school autism have adequate facilities. To support the needs of an autistic child, then in the planning and designing of the school applies the principles of Universal Design. The goal in planning and designing school autism is to disclose, formulate, and designing a school building associated with autistic school facilities of the Batang City with an emphasis on Universal Design that is used as a container of autistic children's education activities, along with the supporting facilities. The method used is descriptive method and dokumentatif, that is by way of collecting primary files as well as secondary files. Design an autistic school in the Batang City in accordance with the standard facilities that are used to educate an autistic child to the concept of Universal Design, as well as with good security. The results of this design would be no building of medical center, that provides therapists and medical facilities to deal with the children of learners who are in the school. There is also a Building Manager and Academic Classroom Building, serta Skill Classroom Building, designed with the concept of Contemporary Modern architecture buildings.